Radiation Quality, Like Art, Consists in Drawing the Line Somewhere - Kunos, Charles; Petersen, Ivy A. (Frontiers in Oncology, 2013)
Summary The architects of phase I radiochemotherapy development programs impose a semblance of structured radiation ‘intensity’ and adverse event predictability upon radiation-anticancer agent interactions whose natural complexity and improper mixing would otherwise lead to dire health consequences. It is incumbent upon radiation oncology investigators to pledge radiation quality and safety to the participants of radiochemotherapy trials. Measures of radiation quality and safety may be tools to scrutinize radiation-anticancer agent dose and schedule, as well as, radiation field design among diverse radiation delivery platforms. In this article, the merits and demerits of phase I radiochemotherapy quality and safety policies are critiqued considering the current era of rapidly evolving radiation technologies.